Pengaruh Sumber Pembiayaan Pendidikan terhadap Peningkatan Hasil Belajar Siswa di SMA Negeri 7 Manado - Shelty Deity M Sumual; Sjeddie Rianne Watung; Febryani M. L. Rattu; Allen A. Ch. Manongko (Society, 2021)
This research aims to determine the source of education funding and the magnitude of the influence of these sources of educational funding on student learning outcomes. The expected benefits from this research include practical benefits, which can serve as a reference for readers and become a means for this research to explore economic education theories, and theoretical benefits as inputs for Education Office. This research used a descriptive method with correlational techniques, in which the data collected were analyzed with a correlation formula. The population was all students who received BKM (Bantuan Keluarga Miskin or Poor Family Assistance) scholarships, and the sample was taken from the entire population. The research results showed that students’ average potential was satisfactory, and education funding significantly influenced student achievement. Apart from the education funding factors, learning achievement is also determined by other factors, such as student perseverance.